1999
DOI: 10.1046/j.1525-1373.1999.d01-41.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Mechanisms of Tea Against Heterocyclic Amine Mutagens from Cooked Meat

Abstract: Cooking meat and fish under normal conditions produces heterocyclic amine mutagens, several of which have been shown to induce colon tumors in experimental animals. In our search for natural dietary components that might protect against these mutagens, it was found that green tea and black tea inhibit the formation of heterocyclic amine-induced colonic aberrant crypt foci (ACF) in the rat. Since ACF are considered to be putative preneoplastic lesions, we examined the inhibitory mechanisms of tea against the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 25 publications
(18 reference statements)
0
10
1
1
Order By: Relevance
“…However, coffee contains many lipids that tea does not and these may reduce colon cancer risk through an effect on intestinal transit time and bile secretion (Giovannucci, 1998;Boekema et al, 1999). On the converse side and in contrast to the results of this study, tea contains many antioxidants and has been demonstrated in laboratory studies to have anticarcinogenic effects in the colon (Nasani et al, 1998;Dashwood et al, 1999;Xu and Dashwood, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…However, coffee contains many lipids that tea does not and these may reduce colon cancer risk through an effect on intestinal transit time and bile secretion (Giovannucci, 1998;Boekema et al, 1999). On the converse side and in contrast to the results of this study, tea contains many antioxidants and has been demonstrated in laboratory studies to have anticarcinogenic effects in the colon (Nasani et al, 1998;Dashwood et al, 1999;Xu and Dashwood, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…These compounds are called an``interceptor molecule''. [40][41][42] g) Angiogenesis and anti-angiogenic action: The question of whether preneoplasias or early stage tumors can continue to grow to a large extent is dependent on the availability of nutrients to sustain anabolism. This in turn will require a su‹cient blood supply and because of the generally solid nature of focal lesions, angiogenesis and therefore anti-angiogenic agents may clearly be of importance.…”
Section: Processes and Potential For Preventive Actionmentioning
confidence: 99%
“…13); Green tea polyphenols, classiˆed as members of the ‰avonoid group, including epigallocatechin, epicatechin gallate (ECG) and epigallocatechin-3-gallate (EGCG) have been shown to inhibit carcinogenesis in many organs. 41,108,[113][114][115][116] Anti-oxidant activity, apoptotic potentials to carcinogen-initiated and interaction to cell cycle are the mechanism for the inhibitory eŠects. EGCG inhibits AP-1 activity in the epidermis of a transgenic mouse model.…”
Section: Processes and Potential For Preventive Actionmentioning
confidence: 99%
“…Ингибирование метаболической активации ГА, например, за счёт инактивации цитохромов Р450 приводит к снижению уровня мутагенных молекул и антиканцерогенному эффекту. Обнаружено, что таким образом действуют некоторые полифенолы, в частности, катехины чая [23,24]. Ресвератрол с различной эффективностью ингибирует активность цитохромов CYP1A2, CYP1A1 и CYP1B1, с чем связывают его защитное действие против гетероциклических аминов, а также против ароматических аминов, полициклических ароматических углеводородов (ПАУ), генотоксичных катехоловых метаболитов эстрогена [25][26][27].…”
Section: рисунокunclassified